PARADIGMA RISET DALAM PEMASARAN (Fokus Ekonomi, 2009)
This paper aims to paradigmatically identify the developments within the field of consumer research. Paradigms in consumer research can be broadly classified as a set of fundamental assumptions that researchers make about what they are studying and how they study it. There are two paradigms within the field of consumer research: the positivistic and the non-positivistic. The study of consumer behavior is rapidly evolving as researchers recognize and implement new techniques and trans- disciplinary perspectives to understand the nature of purchase and consumption behavior.